Feedback from ionised gas outflows in the central kpc of nearby active galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - David, Edwin; Storchi-Bergmann, Thaisa
Abstract: We use integral-field spectroscopy obtained with the Gemini instrument GMOS-IFU (Gemini Multi-Object Spectrograph Integral Field Unit) to map the gas distribution, excitation and kinematics in the central kpc of 11 nearby active galaxies. We use channel maps to quantify the ionised gas masses, mass outflow rates and powers of the outflows in order to gauge the feedback effect of these outflows on the host galaxies. We compare this method with others previously used to calculate the feedback power of such outflows.